Long-acting liposomal corneal anesthetics. (October 2018) - Zhan, Changyou; Santamaria, Claudia M.; Wang, Weiping; McAlvin, J. Brian; Kohane, Daniel S.
Abstract: Eye drops producing long-acting ocular anesthesia would be desirable for corneal pain management. Here we present liposome-based formulations to achieve very long ocular anesthetic effect after a single eye drop instillation. The liposomes were functionalized with succinyl-Concanavalin A (sConA-Lip), which can bind corneal glycan moieties, to significantly prolong the dwell time of liposomes on the cornea. sConA-Lip were loaded with tetrodotoxin and dexmedetomidine (sConA-Lip/TD), and provided sustained release for both. A single topical instillation of sConA-Lip/TD on the cornea could achieve 105 min of complete analgesia and 608 min of partial analgesia, which was significantly longer than analgesia with proparacaine, tetrodotoxin/dexmedetomidine solution or unmodified liposomes containing tetrodotoxin and dexmedetomidine. sConA-Lip/TD were not cytotoxic in vitro to human corneal limbal epithelial cells or corneal keratocytes. Topical administration of sConA-Lip/TD provided prolonged corneal anesthesia without delaying corneal wound healing. Such a formulation may be useful for the management of acute surgical and nonsurgical corneal pain, or for treatment of other ocular surface diseases.